Five-Year Inpatient Management of Teenagers With Anorexia Nervosa: Focus on Nutritional Issues. Issue 5 (May 2022) - Trovato, Chiara Maria; Capriati, Teresa; Bolasco, Giulia; Campana, Carmen; Papa, Valentina; Mazzoli, Bianca; Zanna, Valeria; Marchili, Maria Rosaria; Basso, Maria Sole; Maggiore, Giuseppe; Diamanti, Antonella
ABSTRACT: Objectives: In patients with Anorexia Nervosa (AN) malnutrition can lead to life-long nutritional treatments. The refeeding process can combine natural feeding (NF) with specific nutritional strategies, including oral nutritional supplements (ONS) and nasogastric feeding (NGF). Aims of the present study were to assess the efficacy of hospital protocol and identify the most effective inpatient nutritional strategies for weight restoration. Methods: All patients hospitalized from April 2015 to April 2020 were enrolled. According to hospital protocol, NF was proposed to all patients; ONS were combined with NF if caloric intake was <70% of the requirements and NGF was added if caloric intake did not reach 30% in the first week from admission. Results: Overall, 186 patients [M = 20; median age 14 (interquartile range 1316)] were included. Nutritional issues were the main indication to admission (56.6%). A significant effect of combination treatment, with a shorter duration of hospitalization when using ONS with NGF in addition to NF was found (ß : —20.28 [95% confidence interval —34.92:—5.65], P   <  0.001). Only one patient showed a significant but limited increase of liver enzymes. Conclusions: We provide a safe and effective standardized protocol to treat the malnutrition of teenagers with AN in an inpatient setting. Malnutrition was the most important cause of admission, and more than half of the patients admitted were severely malnourished. The combination of NF, ONS, and NGF was the most effective strategy to achieve the weight restoration; however, this result should be validated on larger series of patients treated with NGF and NF.